Structure and Function of HLA-A*02-Restricted Hantaan Virus Cytotoxic T-Cell Epitope That Mediates Effective Protective Responses in HLA-A2.1/Kb Transgenic Mice - Ma, Ying; Cheng, Linfeng; Yuan, Bin; Zhang, Yusi; Zhang, Chunmei; Zhang, Yun; Tang, Kang; Zhuang, Ran; Chen, Lihua; Yang, Kun; Zhang, Fanglin; Jin, Boquan (Frontiers in Immunology, 2016)
Hantavirus infections cause severe emerging diseases in humans and are associated with high mortality rates; therefore, they have become a global public health concern. Our previous study showed that the CD8+ T-cell epitope aa129-aa137 (FVVPILLKA, FA9) of the Hantaan virus (HTNV) nucleoprotein (NP), restricted by human leukocyte antigen (HLA)-A*02, induced specific CD8+ T-cell responses that controlled HTNV infection in humans. However, the in vivo immunogenicity of peptide FA9 and the effect of FA9-specific CD8+ T-cell immunity remain unclear. Here, based on a detailed structural analysis of the peptide FA9/HLA-A*0201 complex and functional investigations using HLA-A2.1/Kb transgenic mice, we found that the overall structure of the peptide FA9/HLA-A*0201 complex displayed a typical MHC class I fold with Val2 and Ala9 as primary anchor residues and Val3 and Leu7 as secondary anchor residues that allow peptide FA9 to bind tightly with an HLA-A*0201 molecule. Residues in the middle portion of peptide FA9 extruding out of the binding groove may be the sites that allow for recognition by T cell receptors. Immunization with peptide FA9 in HLA-A2.1/Kb transgenic mice induced FA9-specific cytotoxic T cell responses characterized by the induction of high expression levels of IFN-γ, TNF-α, granzyme B, and CD107a. In an HTNV challenge trial, significant reductions in the levels of both the antigens and the HTNV RNA loads were observed in the liver, spleen and kidneys of transgenic mice pre-vaccinated with peptide FA9. Thus, our findings highlight the ability of HTNV epitope-specific CD8+ T-cell immunity to control HTNV and support the possibility that the HTNV-NP FA9 peptide, naturally processed in vivo in an HLA-A*02-restriction manner, may be a good candidate for the development HTNV peptide vaccines.